1969
DOI: 10.2134/agronj1969.00021962006100010040x
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Composition of Six Tropical Grasses as Influenced by Plant Age and Nitrogen Fertilization

Abstract: This study was conducted in central Brazil on a sandy loam soil which under normal conditions receives no fertilizer. The K, P, Ca, Mg, Cu, Mn, Fe, and Zn contents were determined on six grasses: Meilinis minutiflora Beauv., Digitaria decumbens Stent., Pennisetum purpureum Schum., Pennistetum clandestinum Hochst., Cynodon dactylon Pers., and Panicum maximum Jacq. var. ‘Gondlyodes Doell’ Significant decreases in K, P, Mg, Cu and Fe in the forages (P < .01) occurred with advance in plant age from 4 to 36 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
8
1
9

Year Published

1980
1980
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 1 publication
8
8
1
9
Order By: Relevance
“…Forage K was low in the southeast region during the dry season, averaging .27%. Similar K forage seasonal variations have been reported previously (Gomide et al, 1969 Differences (P<.05) in forage carotene concentrations were found between seasons (17.6 ppm in the wet season vs 1.2 ppm in the dry season) and among regions (6.0 to 16.3 ppm). Forage carotene was at low concentrations during the dry season, with all but one ranch averaging less than 2 ppm.…”
Section: Mean Forage P Concentrations In Florida Pasturessupporting
confidence: 88%
“…Forage K was low in the southeast region during the dry season, averaging .27%. Similar K forage seasonal variations have been reported previously (Gomide et al, 1969 Differences (P<.05) in forage carotene concentrations were found between seasons (17.6 ppm in the wet season vs 1.2 ppm in the dry season) and among regions (6.0 to 16.3 ppm). Forage carotene was at low concentrations during the dry season, with all but one ranch averaging less than 2 ppm.…”
Section: Mean Forage P Concentrations In Florida Pasturessupporting
confidence: 88%
“…An increase in the trace element content of plants in the wet season has been observed for pastures in the Kenya highlands (Howard et al 1962), for grass species adjacent to Lake Nakuru in the Rift Valley (Maskall 1991) and for several grass and browse species in Mole National Park" in Ghana (Bowell & Ansah 1993). Trace element concentrations in tropical pastures can fall as the plant matures (Gomide et al 1969) and during periods of rapid growth (Fleming 1973). Significant differences in trace element content can occur between plant species in tropical areas, particularly between grasses and browse plants (Tartour 1966;Reid et al 1979;Ben-Shahar & Coe 1992).…”
Section: Soil-plant Uptake Of Trace Elementsmentioning
confidence: 99%
“…In most circumstances, Zn declines as plants mature (Mayland, 1975;McDowell, 1997). Gomide et al (1969) reported significant differences in forage Zn concentrations between two consecutive years. Climate may influence plant concentrations, as prevalence of Zn deficiency in cool, wet seasons has been associated with decreased solubility of soil Zn (Reuter, 1975).…”
Section: Natural Sourcesmentioning
confidence: 92%